Investigation on niobium oxide coatings for protecting and enhancing the performance of Ni cathode in the MCFC. (2nd November 2016) - Meléndez-Ceballos, A.; Fernández-Valverde, S.M.; Albin, V.; Lair, V.; Chávez-Carvayar, J.Á.; Ringuedé, A.; Cassir, M.
Abstract: This study addresses the problem of the nickel cathode dissolution, decreasing the lifetime of molten carbonate fuel cells, by a protective coating of Nb2 O5 processed by atomic layer deposition ALD onto the porous cathode substrate. Samples of different thicknesses were tested electrochemically in molten Li2 CO3 -K2 CO3 eutectic at 650 °C during 230 h by means of chronopotentiometry and electrochemical impedance spectroscopy. A significant decrease in the stabilization time with respect to the oxygen reduction potential is observed with niobium coatings, which could indicate an electrocatalytic process favoured by the presence of Nb. The structure and morphology of the coated samples are characterised by XRD, SEM and XPS before and after the electrochemical tests. Mixed lithiated Ni and Nb oxides are likely to be formed at the cathode surface. Interestingly, this Nb-containing mixed oxide not only can protect Ni cathode but also maintains its good performance. Highlights: Thin films (5, 20, 50 and 300 nm) of Nb2 O5 deposited by ALD technique on Porous nickel. XRD, SEM and XPS characterization. OCP and impedance measurements in Eutectic lithium-carbonate melt. Best results with 20 nm thin film.